Digital Transformation in Hisab Rukyat: A Sociological Perspective on Integrating Information Technology in Islamic Astronomical Tradition - Encup Supriatna (International Journal of Science and Society, 2023)
This research investigates how the integration of Information Technology (IT) in the practice of Hisab Rukyat, a traditional method in Islamic astronomy for determining prayer times, is transforming the social and cultural landscape in Muslim communities. Employing a qualitative approach, the study collected data through in-depth interviews, participatory observations, and analysis of documents related to the Hisab Rukyat bodies in various countries. Findings indicate that the adoption of IT not only enhances accuracy and efficiency in astronomical calculations but also sparks sociological debates over balancing technological innovation with tradition. Furthermore, the study identifies shifts in community dynamics, where younger generations are more receptive to technological use, while older ones tend to adhere to traditional methods. These findings suggest that while IT provides a more efficient means for calculations, an intergenerational dialogue is also necessary to maintain cultural continuity in this digital transition. The implications of this study are significant for policymakers, religious communities, and academics interested in the interplay between technology, society, and religious traditions.